How does the religion profile of European countries impacts on terrorism attacks in the new century? - Laureano, Raul M. S.; Abreu, M. E.; Laureano, L.; Morais, Ana Isabel F. (ESA Sociology of Religion Research Network Conference: Religion in the Public Domain, 2014)
Terrorism stands as one of the most aggressive forms of organized crime, either by the means it uses or the purposes which aims to achieve. Terrorism distinguishes itself from overall organized crime by acting upon motivations of political, ideological and religious order, without an ultimate goal of obtaining financial compensation. Some empirical studies disqualify the dominant perspective of a strong direct correlation between religion and terrorism. Although the religion characterization of a country is important in explaining terrorism, it shows less relevance than other explanatory dimensions (e.g., socio-demographic, political and economic). In this study we collected data from the Global Terrorism Database for the terrorism measures: number of attacks; target information; number of fatalities; and number of injured. From the Quality of Government Dataset we built the religion measures: religious fractionalization; percentage of Protestants; percentage of Catholics; percentage of Muslims; and percentage of population belonging to other denominations. The sample comprises data for 33 European countries from 2000 to 2010. Performing cluster analysis the countries were classified in four groups regarding their religious characteristics and the relation of the country profile with each terrorism measure was analysed. The results show that religion accounts for terrorism incidents in European countries. As a counter-terrorism strategy the policy advice relies on promoting religious fellowship and reducing social discrimination. Moreover, higher knowledge on the determinants of terrorism provides additional support to the development of guidelines on the interventions for the prevention, detection and reversal of processes of radicalization which are likely to generate violence.